2014
DOI: 10.1001/jamapediatrics.2013.4521
|View full text |Cite
|
Sign up to set email alerts
|

Commercialism in US Elementary and Secondary School Nutrition Environments

Abstract: Most US elementary, middle, and high school students attend schools where they are exposed to commercial efforts aimed at obtaining food or beverage sales or developing brand recognition and loyalty for future sales. Although there have been significant decreases over time in many of the measures examined, the continuing high prevalence of school-based commercialism calls for, at minimum, clear and enforceable standards on the nutritional content of all foods and beverages marketed to youth in school settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
0
40
1
2
Order By: Relevance
“…Environmental change interventions that may influence SSB consumption have generally targeted SSB availability in schools, stores, and public places, as well as advertising that targets children (28,116,136,151). However, the greatest consumption of SSBs for children and adults happens in the home.…”
Section: Institute Of Medicine Report On Obesity Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental change interventions that may influence SSB consumption have generally targeted SSB availability in schools, stores, and public places, as well as advertising that targets children (28,116,136,151). However, the greatest consumption of SSBs for children and adults happens in the home.…”
Section: Institute Of Medicine Report On Obesity Preventionmentioning
confidence: 99%
“…Public health researchers and advocates have continued to monitor how well marketing and advertising follow these principles and have indicated that there is still room for improvement (72,80,99). Of note, after significant advocacy in this arena, advertisements for SSBs have decreased in recent years, although rates still remain very high for children from low socioeconomic backgrounds and certain racial/ethnic groups (64,136).…”
Section: Limit Marketing Of Ssbs and Minimize Marketing's Impact On Cmentioning
confidence: 99%
“…Most students are exposed to at least one form of marketing during the school day (5,6). In 2009, food and beverage companies spent $149 million on marketing foods and beverages in US schools (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., significant numbers of children are exposed to food and beverage marketing materials at school; over 70% of students in elementary through high schools attend a school that contains food and beverage marketing in the form of vending, advertising, and/or use of coupons as incentives. The highest prevalence of this marketing targeted at lower-income students, among whom the prevalence of sweetened beverage intake is the highest (Han & Powell, 2013;Johnston, Delva, & O'Malley, 2007;Terry-McElrath, O'Malley, & Johnston, 2013;Terry-McElrath, Turner, Sandoval, Johnston, & Chaloupka, 2014). Food and beverage advertising is known to influence food selection and consumption among children and the availability of food and beverage products in schools is related to greater consumption, at least in some groups of students (Blum et al, 2008;Johnston et al, 2007;Terry-McElrath et al, 2013).…”
Section: Sweeteners During Childhoodmentioning
confidence: 99%